Optimal Discharge Education: Evidence for Enhancing Family Preparedness for Premature Infants - Zhang L; He J; Zhou Y; Li X (Journal of Multidisciplinary Healthcare)
Lingping Zhang,1,2 Junjie He,3 Yue Zhou,3 Xiaomei Li1 1School of Nursing, Health Science Center, Xi’an Jiaotong University, Xi’an, Shaanxi, People’s Republic of China; 2Department of Neonatology, Children’s Medical Center, the Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, People’s Republic of China; 3Department of Pediatrics, Southwest Medical University, Luzhou, Sichuan, People’s Republic of ChinaCorrespondence: Xiaomei Li, School of Nursing, Health Science Center, Xi’an Jiaotong University, #76, Yanta West Road, Xi’an, Shaanxi, 710061, People’s Republic of China, Email roselee@xjtu.edu.cnObjective: The study aimed to systematically search, screen, evaluate, and synthesize evidence regarding the effectiveness of discharge education in enhancing family preparedness for premature infants. The ultimate goal was to provide evidence-based references for implementing discharge education for family caregivers, thereby improving families’ discharge readiness and enhancing home care and infant health.Methods: Systematic searches were conducted across BMJ Best Practice, UpToDate, the Cochrane Library, and other relevant databases from October 2014 to October 2024. The collected literature comprised clinical decisions, guidelines, expert consensuses, systematic reviews, meta-analyses, best practices, and randomized controlled trials related to discharge education for enhancing family preparedness for premature infants. Relevant evaluation tools were selected based on the type of literature to assess methodological quality, and the evidence was extracted, summarized, and organized.Results: A total of 1724 documents were searched. Ultimately, ten pieces of literature were selected based on the inclusion and exclusion criteria, comprising one clinical decision, one guideline, one expert consensus, two systematic reviews, one meta-analysis, one best practice, and three randomized controlled trials. From these literature, a total of thirty-three pieces of evidence were extracted and synthesized across five domains: assessment, planning, implementation, evaluation, and support.Conclusion: This study synthesized evidence on discharge education for premature infant’ families, revealing key insights for clinical practice. It emphasized tailored education plans, early family involvement, multidisciplinary collaboration, and diverse teaching methods. Implementing these practices is expected to improve families’ discharge readiness, thereby promoting better infant health.Keywords: discharge education, family preparedness, premature infants, evidence synthesis